KAJIAN KOMPETISI TUMBUHAN EKSOTIK YANG BERSIFAT INVASIF TERHADAP POHON HUTAN PEGUNUNGAN ASLI TAMAN NASIONAL GUNUNG GEDE PANGRAN - Budi Utomo; Cecep Kusmana; Sukisman Tjitrosemito; Muhammad Nur Aidi (Institut Pertanian Bogor (IPB University), 2007)
Up to now, montane rain forest of Gunung Gede-Pangrango National Park, faces problem in the form of invasion of exotic plant species into the area. Location of the area that borders with various land uses, such as Botanical Garden and agricultural land, make it very susceptible toward invasion of plant species from outside the area. The collapse of large trees which normally constitute a mechanism of natural regeneration, was in fact stimulating the development of exotic species, particularly those which were invasive, inside the area. The objective of this research was to test the competitive ability of endemic species, which in this case was represented by Cleystocalyx operculata and Mischocarpus pentapetalus, toward exotic plant species, represented by Austroeupatoriun inulaefolium and Passiflora ligularis, during 5 months of study. Growth rate of exotic plant species, as well as the dry weight biomass, were larger than those of endemic species. Indirect estimation of competitive ability showed that competitive ability (β) of endemic species were 4-5 times less, namely 0.0274 (for C. operculata) and 0.0251 (for M. pentapetalus); as compared with those of exotic species, namely 0.125 (for P. ligularis) and 0.1104 (for A. inulaefolium). Direct test also proved that competitive ability (β) of endemic species was lower than that of exotic species, as shown by relative crowding value < 1. Estimation of future competitive ability, using diagram of input/ output ratio, showed also the disability of endemic species to compete with exotic species, where position of input/output ratio points were parallel with equilibrium line y=x. Considering those facts, there is urgent need for controlling these invasive exotic species inside the National Park area to maintain the sustainability of biodiversity and regeneration of endemic species in montane rain forest of Gunung Gede–Pangrango National Park.